A Review of the Ethnopharmacology, Phytochemistry, Pharmacology, Application, Quality Control, Processing, Toxicology, and Pharmacokinetics of the Dried Rhizome of Atractylodes macrocephala - Yang, Liu; Yu, Huan; Hou, Ajiao; Man, Wenjing; Wang, Song; Zhang, Jiaxu; Wang, Xuejiao; Zheng, Senwang; Jiang, Hai; Kuang, Haixue (Frontiers in Pharmacology, 2021)
The product investigated herein is the dried rhizome of Atractylodes macrocephala Koidz. [Asteraceae] (Baizhu), which is also known as Dongbaizhu, Wuzhu, Yuzhu, Zhezhu, and Zhongzhu, among others. It invigorates the spleen, replenishes qi, and removes dampness, diuresis, and hidroschesis, and impacts fetal safety. It is often used for the treatment of diseases such as spleen function deficiency, abdominal distension, diarrhea, sputum, vertigo, edema, fever, and sweating and also aids cessation of minimal vaginal bleeding during pregnancy. In this study, research pertaining to the ethnopharmacology, application, phytochemistry, analytical methods, quality control, processing, pharmacology, toxicology, and pharmacokinetics of Baizhu has been reviewed. Relevant information and data reported for Baizhu were collected from CNKI, VIP, PubMed, Web of Science, scientific databases, Chinese Medicinal Material Encyclopedia, Chinese herbal medicine classics, Chinese medicine dictionary, doctoral and master’s theses, and so on. Baizhu demonstrates diuretic, antidiuretic, anti-inflammatory effects and antitumor function and aids regulation of gastrointestinal function, hypoglycemic effect, analgesic action, protection on the liver ischemia-reperfusion injury (IRI) in rats, inhibition of aromatase, treatment of bone disease, strengthening myocardial contraction ability, detoxification and cholagogic effect, fall hematic fat action, such as the treatment of acute renal injury, and so on. It also can be an anticoagulant, improve the nervous system disease, affect the immune system, and regulate uterine smooth muscle, antioxidation, antiaging, and antibacterial effect. Sesquiterpenoids, triterpenoids, polyacetylenes, phenylpropanoids, coumarins, flavonoids, flavonoid glycosides, steroids, benzoquinones, polysaccharides, and other compounds were isolated from Baizhu. Among them, sesquiterpenoids, polysaccharides, and polyacetylenes are the main components of Baizhu. Baizhu exhibits a wide range of pharmacological effects and constitutes a considerable proportion of the composition of many proprietary crude drugs. It mainly affects the endocrine, nervous, and urinary systems. The presented information suggests that we should focus on the development of new drugs related to Baizhu, including specific components, to achieve a greater therapeutic potential that can be considered to further explore the information related to Baizhu.